FINANCIAL STABILITY IN AGRICULTURAL ENTERPRISES IN THE CONDITIONS OF THE DIGITAL ECONOMY AND THE EFFECTIVENESS OF INCREASING PROFITS - Turop Djumanov (Scholar Express Journals, 2023)
In this article, financial stability in agricultural enterprises of the Republic of Uzbekistan is the economic content of profit, that is, profit is a generalizing indicator of financial and economic activity of enterprises and the main source of increasing production efficiency. Its size depends on the quantitative and qualitative results of enterprises, the volume of production and sale, its quality improvement, the reduction of cost, the increase in labor productivity and others, and also studies economic and organizational aspects. It analyzes the investment attractiveness of the industry, as well as the success of reforms carried out on the basis of the conclusions of international experts. The purpose of this article is to assess the effectiveness of the activities of Republican agricultural farms. In addition, the author gives recommendations on the further development of rural areas in Uzbekistan on the example of beneficial results of foreign countries
Keywords: Profit; enterprise; cotton raw materials